Analisis Peran Emosi Positif Sebagai Mediator Gaya Hidup Berbelanja Dan Motivasi Berbelanja Hedonis Terhadap Pembelian Impulsif Di E-Commerce - Mukmin Setiadi; Anny Nurbasari (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
The growth of E-commerce in Indonesia has provided significant benefits to society, particularly in terms of convenience in shopping and access to a wider range of products. The research aims to in-vestigate the role of positive emotions as a mediator between shopping lifestyle and hedonic shopping motivation on impulse buying behavior in E-commerce. This study employs a quantitative method. The population consists of consumers who have made purchases on E-commerce platforms. The sample includes consumers who have exhibited impulsive characteristics in their transactions over the last 6 months. Primary data for this research was collected through distributing questionnaires via Google Forms to respondents. The target respondents are students in Bandung who have made at least one purchase on E-commerce platforms. Using SmartPLS 4.0 for Structural Equation Modeling Partial Least Squares (SEM-PLS) analysis, the researcher tested hypotheses. From the hypothesis test-ing, first, shopping lifestyle directly influences positive emotions. Second, positive emotions also signifi-cantly influence impulse buying. Third, shopping lifestyle also has a direct effect on impulse buying. Fourth, no significant influence was found between hedonic shopping motivation and impulsive buy-ing. Fifth, shopping lifestyle mediated by positive emotions significantly influences impulse buying.